AKUNTABILITAS PELAYANAN PUBLIK DALAM PEMBUATAN KARTU TANDA PENDUDUK ELEKTRONIK (E-KTP) DI KANTOR KECAMATAN KREJENGAN KABUPATEN PROBOLINGGO - Muhammad Syaifur Rizal (PT Innovative Academic Journals, 2024)
Accountability is the responsibility for the management of resources and the implementation of policies entrusted to the reporting entity in achieving the established goals periodically, with the assurance that there is no hidden agenda, providing transparent and honest information to the public. To realize good governance, it is crucial to apply principles like accountability in the public service process. The aim of this research is to examine the implementation of public service accountability, specifically in the process of issuing Electronic Identity Cards (E-KTP) at the Krejengan Sub-district Office, Probolinggo Regency. The method used in this study is descriptive research with a qualitative approach. The findings from the research conducted at the Krejengan Sub-district Office, Probolinggo Regency show that, from various accountability indicators, the staff have successfully applied the principle of transparency. However, there were some shortcomings in several sub-aspects of accountability, particularly in the service process for the issuance of Electronic Identity Cards (E-KTP). When the blank forms ran out, the staff did not promptly take action to collect more forms from the Population and Civil Registration Office.